ANALYSIS OF STUDENTS' CREATIVE THINKING IN SOLVING PROBLEMS OPPORTUNITIES BASED ON STUDENTS' LEARNING - Nazilatun Ni'mah; Ali Shodikin (Universitas Muhammadiyah Lampung, 2022)
The purpose of this research is research in creative thinking on student learning with opportunity material. The research method used is a qualitative research method, tajing the subject of class VIII junior high school students in 2021/2022. Based on the results of the discussion on creative thinking skills, students are given to obtain information on creative thinking skills on the opportunity material that has been taught.